Equilibrium concentration of kinks on the SB steps of the Si(100) surface - Yesin, Michail Yu (Journal of surface investigation: X-ray, synchrotron and neutron techniques)
The temperature and time dependences of the concentration of kinks on the S-A and S-B steps perpendicular to the upper-terrace dimer rows on the Si(100) surface with an inclination of 0.5 degrees are established. The numbers of step kinks are determined from atomic-resolution scanning tunneling microscopy images of the stepped Si(100) surface. It is shown that the temperature dependence of the number of kinks has a minimum at 650 degrees C. It is suggested that, at low temperatures, the steps are intensively smoothed (step kinks vanish), while at high temperatures, the step-destruction process (formation of a great number of step kinks) is more intensive. The step smoothing and destruction processes include a sequence of atom and dimer elementary acts. As the annealing time increases, the kink concentration decreases and takes a constant value. The equilibrium step-kink concentration is shown to be determined by the surface annealing temperature and time.